Songlines - soundwalks as a space for memory: Panama City’s Tramway - Alzamora Rivera, Mar (2021)
During the last decades, soundwalks have constituted an aesthetic practice used to get to know a territory culturally. Cities are fascinating settings and their landscapes provide us with a connection that opens a door to sociocultural and political secrets. For years, I have dedicated my artistic research to the interweaving between the city, sound and memory. In this article, I will share my sounding experience while walking on the vanished tramway in Panama City. From these soundwalks, I have determined that each city, as people, has a type of deep scar; they become routes or songlines, which move us without noticing it. What happens to memories when we face the changes in cities? "Songline" is the search for my family heritage mapping the sonic complexities of the tramway.